2000
DOI: 10.1046/j.1365-8711.2000.03510.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectra of a large sample of quasars with ASCA

Abstract: A B S T R A C TThe results from an X-ray spectral analysis of a large sample of quasars, observed with ASCA, are presented. The sample was selected to include all ASCA observations of quasars, with z . 0X05 and M V , 223X0Y available up to 1998 January. The data reduction leaves 62 quasars, 35 of which are radio-loud and 27 radio-quiet, suitable for spectral analysis. Differences are found between the radio-quiet quasars (RQQs) and the radio-loud quasars (RLQs): the RLQs have flatter X-ray spectra G , 1X6Y wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

118
479
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(605 citation statements)
references
References 53 publications
118
479
7
Order By: Relevance
“…Our findings are also consistent with previous results showing low levels of reflection for high-redshift quasars (Vignali et al 1999;Reeves & Turner 2000;Page et al 2005), although we note that Ricci et al (2011) found higher levels of reflection from Seyfert2s than from Seyfert1s. Figure 8 (bottom panels) shows unobscured and obscured sources as empty and filled data points, respectively, and does not allow a firm conclusion on this point for Seyfert-like luminosity sources.…”
Section: The Reflection Componentsupporting
confidence: 94%
“…Our findings are also consistent with previous results showing low levels of reflection for high-redshift quasars (Vignali et al 1999;Reeves & Turner 2000;Page et al 2005), although we note that Ricci et al (2011) found higher levels of reflection from Seyfert2s than from Seyfert1s. Figure 8 (bottom panels) shows unobscured and obscured sources as empty and filled data points, respectively, and does not allow a firm conclusion on this point for Seyfert-like luminosity sources.…”
Section: The Reflection Componentsupporting
confidence: 94%
“…Based on ROSAT data, Boller, Brandt, & Fink (1996) and Laor et al (1997) found a significant correlation between the X-ray photon indexes of radio-quiet AGNs and the value for the FWHM H , where those AGNs with the narrowest broad Balmer lines, narrow-line Seyfert 1 galaxies (NLS1s), tended toward the steep end of the distribution of C. Subsequent work with ASCA in the 2-10 keV band has extended this finding to higher energy, although the spread of C in the 2-10 keV band is much smaller (e.g., Brandt, Mathur, & Elvis 1997;Reeves & Turner 2000). Mrk 231 has relatively narrow Balmer emission lines, FWHM H ¼ 2870 km s À1 (Boroson & Meyers 1992) and FWHM H ¼ 3000 km s À1 (Lípari, Terlevich, & Macchetto 1993), particularly for a QSO of its luminosity.…”
Section: X-ray Variability and Spectral Resultsmentioning
confidence: 99%
“…In particular, there were positive residuals below 1.0 keV and above 5 keV. Also, the best-fitting photon index, À ¼ 0:46 AE 0:09, was unusually hard; the typical photon index for a radio-quiet QSO is in the range À ¼ 1:7-2.3 (e.g., Reeves & Turner 2000;George et al 2000). As Mrk 231 hosts a starburst ring within 1 00 of its nucleus (Bryant & Scoville 1996;Carilli et al 1998;Taylor et al 1999), a plausi- ble additional component to add is a Raymond-Smith thermal plasma (Raymond & Smith 1977).…”
Section: Basic Spectral Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…MCG -6-15-30 (Reynolds et al 1997). Also a recent study of the X-ray spectra of AGN with X-ray luminosity range between 10 41 erg s −1 and 10 47 erg s −1 did not reveal any trend in the X-ray slope with the luminosity (Reeves & Turner 2000).…”
Section: Introductionmentioning
confidence: 85%